Peran Kepala MAN 3 Tangerang dalam Upaya Peningkatan Disiplin Guru - Anis Fauzi; Machdum Bachtiar; Syarif Budiman (Journal on Education, 2023)
The purpose of this study is to describe the leadership role of the Madrasah Principal in improving teacher discipline at MAN 3 Tangerang. The focus of this research is why the principal's leadership role in improving teacher discipline at MAN 3 Tangerang is not optimal. In this study used descriptive qualitative whose purpose is to study the state of nature or the natural environment at the research location. The study found that the implementation of leadership by the head of MAN 3 Tangerang was marked by several efforts, including; (a) protection of school interests and goals, (b) group cooperation to achieve school goals, (c) awareness of rights and responsibilities, (d) suggestions, opinions and criticism, (e) freedom for subordinates to work and develop, and f) prudent approach. The leadership of the madrasa head in improving teacher discipline not maximal, because the teachers no quickly understand of school head's vision of work discipline. The indicator can be in the form of the presence of several teachers who lack discipline in following the madrasa rules that have been mutually agreed upon.